Interethnic marriages and their economic effects - Delia Furtado; Stephen Trejo (Institute for the Study of Labor (IZA), 2012)
Immigrants who marry outside of their ethnicity tend to have better economic outcomes than those who marry within ethnicity. It is difficult, however, to interpret this relationship because individuals with stronger preferences for ethnic endogamy are likely to differ in unobserved ways from those with weaker preferences. To clarify some of the complex issues surrounding interethnic marriage and assimilation, this chapter starts by considering the determinants of intermarriage, proceeds with an examination of the economic consequences of intermarriage, and ends with a discussion of the links between intermarriage, ethnic identification, and measurement of long-term socioeconomic integration.
urn:nbn:de:101:1-201206146829
Keywords: J12; J15; J61; 330; intermarriage; immigration; ethnicity